In‐depth approach to fire investigations: microstructural analysis of metallic materials. (30th July 2014) - Boniardi, Marco; Casaroli, Andrea
Summary Failure analysis normally requires many forms of investigation, but visual examination is the most used amongst all possible techniques. However, as the legal climate for fire investigation is becoming more rigorous, fire researchers need to work differently. In other words, to be technically defensible, expert testimony must be built on scientific data. To this aim, in‐depth microstructural analyses of materials are particularly suitable to define the fire scene. This paper discusses some of the basic metallurgical theories used in failure analysis of copper, steel and aluminium alloy components involved in fire situations. Some components that can be easily found in fire and arson scene were submitted to simulated fire for indicated time and temperature. The collected samples were than examined by optical microscopy, scanning electron microscopy and energy‐dispersive spectroscopy. Oxidation, recrystallization, second‐phase precipitation and melting were some of the features observed on samples that can be strictly related to the thermal effect of fire. On the basis of these metallurgical results and starting from the evidence that different exposure temperatures can induce different metallurgical modifications, it is possible to define the temperature range experienced by various components, thus suggesting the fire dynamic during the incident. Copyright © 2014 John Wiley & Sons, Ltd.